Criminalization Of Ai-Generated Child Sexual Abuse Material (Csam): Challenges Of Evidentiary Proof And Jurisdictional Limits In Indonesian Criminal Law - Asep Hermawan; Agustiana (Journal Evidence Of Law, 2025)
The rapid acceleration of generative Artificial Intelligence (AI) has significantly disrupted the cybercrime landscape, giving rise to new forms of morality-based offenses in the form of synthetically created Child Sexual Abuse Material (CSAM), commonly referred to as AI-generated CSAM. In contrast to conventional CSAM, which depicts real physical exploitation of child victims, synthetic CSAM reproduces hyper-realistic visual content without any empirical actus reus involving actual physical abuse. This article aims to analyze the normative vacuum and juridical challenges in criminalizing AI-generated CSAM within the framework of Indonesia’s positive criminal law system. The analysis focuses on the discourse of digital forensic evidence in judicial processes and the determination of jurisdictional boundaries in criminal law in responding to the borderless nature of cybercrime. Based on normative legal research, the findings indicate the urgency of re-conceptualizing the legal definitions of “victim” and “child pornography” within the Pornography Law, the Electronic Information and Transactions Law (ITE Law), and their harmonization with the criminal law system under Law Number 1 of 2023. Comprehensive reform of penal policy is required to ensure that law enforcement mechanisms are capable of addressing and prosecuting both creators and distributors of AI-generated child sexual exploitation material. Such reform is essential to adapt criminal law to the evolving challenges posed by advanced generative technologies.